Acceptability and shelf-life testing of marketable octopus balls - Jumdain, Rosita T. (Miag-ao, Iloilo University of the Philippines in the Visayas, 2007)
A study was conducted to investigate on the feasibility of local octopus (Octopus vulgaris) as a raw material for the production of new value-added octopus balls. The study was divided into three phases. Phase I involved product development and formulation activities using the recommended steps in the new product development. Phase 2 focused on the determination as to which of the two (2) different packaging materials and methods would maintain the quality, correct moisture content and thedesired flavor and texture profiles of the product during storage. Phase 3 involved product costing and test marketing of the newly formulated product in Zamboanga City in order to determine the commercial feasibility of the product. In Phase I, three formulations or treatments (i.e. Treatments A, B, and C, with octopus meat and flour + cassava starch ratio of 50:50, 60:40 and 70:30, respectively) were tested. Resultsrevealed that Treatment B was the most appropriate treatment to be used for the succeeding analyses. This was because, in terms of acceptability, there were no significant differencebetween Treatments B and C, whereas Treatment A was found to be significantly different from these two treatments. When treatment B octopus ball sample was compared witcommercial squid balls, results indicated that the former was more chewy, juicy, springy, and acceptable than the latter. In terms of the proximate composition of the two samples, octopusballs were found to have higher protein content and slightly higher moisture content than commercial squid balls. However, the lipid contents of both samples do not significantly differthe carbohydrate content of the addition, the higher mineral content of octopus implies higher samples and commercial samples are near neutral. After the determination of the appropriate ,product were also developed. The newly developed octopus balls were subjected to shelf life testing. The stability of the product at three different temperatures (i.e. 5 0C, -16 0C, and -21 0C), using two different packaging methods (i.e. sample stored in heat-sealed polyethylene bags and vacuum-packed sample) was determined for 12 weeks. Changes in the samples' moisture content, pH level, microbiological profile (for aerobic and anaerobic organisms, molds and yeasts) and sensory attributes were monitored at regular intervalsShelf life test results showed that storage at -160C and -210C the shelf-life of octopus ball remained stable up to three (3) months of storage. In particular, sensory evaluation of the samples (in terms of general acceptability) showed that the quality of the product on the 12th week of storage was still comparable with freshly prepared sample. In contrast, sample stored at 50C was rejected after storage of 35 days for polyethylene-packed sample and 49 days for vacuum-packedsample. Results also indicated no significant increase in the moisture content of the samples during storage at 5 0C, -160C and -21 0C. In terms of changes in the pH values of the samples, results showed no significant difference between the pH of both the sample in polyethylene bags and the vacuum-packed samples at both -160C and -210C storage temperatures.However, samples stored at 50C showed abrupt decreases in pH values after 14 days for polyethylene-packed and 49 days for vacuum-packed. The results of aerobic, mold and yeast and anaerobic plate counts exhibited minimal growth of organisms in all samples. In addition, the study revealed that the decrease in pH values of the samples was accompanied by an increase in the sensory perceived fishy odor in the samples. A high positive correlation existed between pH and fishy odor. Likewise, there was a high positive correlation between the moisture content and tenderness of the samples when storage at 50C, -160C and -210C because there were no significant changes in the moisture content during storage. There was also high correlation between microbial load and moisture content, pH and odor of the samples. Result of the test marketing of the sample revealed that majority of the consumer (90.72%) very much liked the product. Cost analyses further established the commercial feasibility and marketability of the newly developed octopus balls. .
Thesis (M. S. Fisheries-Fish Processing Technology) -- Miagao, Iloilo : U.P. in the Visayas, October 2007.